Analysis of The Program for Providing Public Space for The Tourism Office in The Development of Tourism Objects - Yulianus Natanuel; Ida Bagus Made Agung Dwi Jatenaya; Musmuliadi Musmuliadi (Publikasi Indonesia, 2022)
For local governments in the context of implementing regional developments, in order to be achieved and sustainable, funding sources are one of the determining factors in achieving the desired goals. This study aims to analyze the implementation of the Gemuruh Waterfall Tourism Object Development Program carried out by the West Kutai Regency Tourism Office and to analyze the obstacles in the implementation of the thundering waterfall tourism object development program. This research is descriptive, conducted at the Department of Tourism, as well as the community of Sekolaq Darat, West Kutai Regency. The time of the implementation of this research was held from September 2020 until the end of 2021. Based on the results of research on the Analysis of the Gemuruh Waterfall Tourism Object Development Program by the Tourism Office of West Kutai Regency, the researchers drew conclusions, namely After each indicator was described, then each result the recapitulation of each of these indicators is combined and the average and percentage are sought, and finally the results of the recapitulation of the overall indicators used as measurements in this study are 68 people or 65.38% of all respondents answered the Implementation of the Waterfall Tourism Object Development Program Rumbling by the Tourism Office is still in the Poor category. It is said to be not good because many tourism object development programs are not running according to the planned activities.